Thermal analysis evaluation of the reactivity of coal mixtures for injection in the blast furnace - Gomes,Maria de Lourdes Ilha (2006)
Pulverized Coal Injection (PCI) is an important standard technology replacing coke partially by pulverized coal into the blast furnace that allows a significant reduction of hot metal costs and environmental impact, contributing to a decrease of coke requirements for ironmaking. Coals typically used in this process in Brazil are, at current time, exclusively imported from many countries, although economic important coal-measures occur in the southern part of the country. The Brazilian coals have a low rank, higher contents of inert components, proportioning nocoking properties and an expected high reactivity. Due to these caractheristics, these coals could be used for injection in the blast furnaces in order to decrease the dependency on high cost imported coals. The efficiency in the combustion and the coal reactivity are considered important parameters in the blast furnace, since a larger amount of char (unburned coal) causes severe problems to the furnace operation. The aim of the present work is to compare the reactivity of a south Brazilian coal, obtained from Faxinal mine, with two imported coals and the blends of the Brazilian coal with the imported ones. The reactivity of these coals and their blends were evaluated in a thermogravimetric analyzer. In the experiments, various mass ratios of Faxinal coal and the imported coals were used to compose the blends. The gasification reaction with pure CO2 was conducted under isothermal conditions at 1050 °C and atmospheric pressure. The experimental results show the greater reactivity of the Faxinal coal. The additive behavior was confirmed. The blends with a composition of up to 50% Faxinal coal have parameters according to the usual limits used for PCI.